Phase-II Trials of Pazopanib in Metastatic Neuroendocrine Neoplasia (mNEN): A Systematic Review and Meta-Analysis - Bongiovanni, Alberto; Liverani, Chiara; Recine, Federica; Fausti, Valentina; Mercatali, Laura; Vagheggini, Alessandro; Spadazzi, Chiara; Miserocchi, Giacomo; Cocchi, Claudia; Di Menna, Giandomenico; De Vita, Alessandro; Severi, Stefano; et al. (Frontiers in Oncology, 2020)
Background Several Phase-II trials have been designed to evaluate Tyrosine Kinase Inhibitor (TKI) and in particular Pazopanib in Neuroendocrine Neoplasia (NEN) but It’s efficacy is not yet demonstrated in a randomised‐controlled Phase III trial. A systematic review of the published clinical trials of metastatic NEN patients could reduce the possible bias of single phase‐II studies. The present systematic review focuses on the efficacy and safety of Pazopanib in metastatic and locally advanced NEN patients. Methods A systematic search in major databases Medline/PubMed, Cochrane, Embase and in supplementary of principal international Meeting swas performed to identify publications on Pazopanib for the treatment of neuroendocrine neoplasia English language was defined as a restriction. Four review authors independently conducted study selection and also assess risk of bias and extract study data. Four published clinical trials and 2 abstract were identified. One trial was excluded because the topic was Von-hippel landau disease and 1 abstract because of the lacking information in meeting resources. Results: In all the trials pazopanib was orally administered at a dose of 800 mg daily continuously with a 28-day cycle. The intention‐to‐treat population for efficacy was 230 patients with a median age of 62 years (range). The partial response rate was 10.7% (95%‐confidence interval, 2,6-20.5%). The rate for stable disease was 79.6% (range: 61.7-92,1%) with a DCR of 90.3%. Progressive disease was reported in 9.7% (5.2-17.6%). No complete response were observed. The median Progression free survival was 11.6 (95% CI: 9.2-13.9) months. Overall survival from all trials was reported at 24.6 (95% CI: 18.7-40.8) months. Severe adverse events (grade III-IV) included hypertension 31%, ast/alt increasing 16%, diarrhoea 10% and fatigue 10%. Conclusions: Pazopanib monotherapy achieved a DCR of 90.3% in patients with locally advanced and/or metastatic Neuroendocrine Neoplasia with a ORR comparable to other Tki and mTOR inhibitor and and safety profile similar to the one of the drugs of the same class.